2020
DOI: 10.1016/j.jclepro.2020.120469
|View full text |Cite
|
Sign up to set email alerts
|

Trading-off ecosystem services for better ecological restoration: A case study in the Loess Plateau of China

Abstract: Balancing trade-offs among multiple ecosystem services (ESs) is critical for restored ecosystem, including the Loess Plateau of China where ESs are undergoing significant changes. In this study, the ESs in Ansai watershed were quantified and analyzed for the period 2000 to 2014 using highresolution and site-specific models. Regression and redundancy analysis were applied to unravel the effects of key drivers on changes in ESs from land use, environmental, and morphological factors and their trade-offs. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 44 publications
1
61
2
2
Order By: Relevance
“…For appropriate ES management, decision makers should consider not only global correlations but also the spatial heterogeneity of the impacts to mitigate unwanted ES trade-offs. In contrast to the findings obtained by using correlation analysis and a global regression model (Feng et al 2020;Zhong et al 2020), our results obtained by the GWR model can reveal the spatial relationship between trade-offs/synergies and the related factors. The intensity of trade-off/synergy relationships was significantly affected by natural factors and socioeconomic factors.…”
Section: Spatially Varying Trade-offs/synergies Among the Ess And Thecontrasting
confidence: 99%
See 1 more Smart Citation
“…For appropriate ES management, decision makers should consider not only global correlations but also the spatial heterogeneity of the impacts to mitigate unwanted ES trade-offs. In contrast to the findings obtained by using correlation analysis and a global regression model (Feng et al 2020;Zhong et al 2020), our results obtained by the GWR model can reveal the spatial relationship between trade-offs/synergies and the related factors. The intensity of trade-off/synergy relationships was significantly affected by natural factors and socioeconomic factors.…”
Section: Spatially Varying Trade-offs/synergies Among the Ess And Thecontrasting
confidence: 99%
“…Previous studies on ESs found that trade-off relationships are ubiquitous (Langner et al 2017;Darvill and Lindo 2016), for example, consider the trade-off between services resulting in the provision of a good (food production, wood production) and regulation services (soil conservation, water purification, regional biodiversity maintenance). Prior findings suggest that ecosystem management should coordinate various ESs to promote their overall benefits (Landuyt et al 2016;Feng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns, international cooperation, i.e., the G-DEP, was proposed. The overall objectives of the G-DEP are to understand the response of dryland ecosystems to global environmental change and to elucidate methods for fostering the development of pathways to support increasing the resilience of socio-ecological systems and the sustainable development in dryland ecosystems (Feng et al, 2020a). Specifically, the goal is to quantify the magnitude and direction of change and the associated responses of dryland ecosystems to the land system and social process and to identify factors controlling the vulnerability and resilience of dryland ecosystems as well as to understand the impact of global environmental change on ecosystem services.…”
Section: Arid and Semi-arid Ecosystems In Africamentioning
confidence: 99%
“…Determining the areas at risk and assessing areas that will be affected have received good feedbacks in China (Feng et al, 2020a). Water, in particular, is a critical factor.…”
Section: Climate Ecosystems and Livelihoods For Sustainable Developmentioning
confidence: 99%
“…In other words, the potential for soil conservation, which can help to measure the room for improvement for soil erosion control in different regions (Gao et al, 2016), was not well considered. Third, although there were some studies focusing on the strategic optimization for the GFG programme that will be useful in the future (Feng et al, 2020; Feng, Wei, & Pan, 2020; Geng et al, 2019; Wen, Deng, & Zhang, 2019), few of them saw the improvement as a dynamic process. In fact, the potential for soil conservation not only shows spatial heterogeneity but it can changed with time.…”
Section: Introductionmentioning
confidence: 99%